Prevalence of Tick-borne Pathogens in Quarantined Dogs at Nakornpranom Animal Quarantine Station, Thailand - Juasook, Amornrat; Boonmars, Thidarut; Sriraj, Pranee; Aukkanimart, Ratchadawan; Jitjuk, Tharadol; Sudsarn, Pukkayanee; Phaetkit, Anothai; Boonjaraspinyo, Sirintip; Maleewong, Wanchai (Journal of Mahanakorn Veterinary Medicine, 2016)
To know the prevalence of tick-borne pathogens in quarantined dogs at Nakhonpranom animal quarantine station, Nakornpranom province, Thailand during September, 2013. About 5% (43 dogs) of EDTA-blood from stray and domestic dogs in Nakhonpranom animal quarantine station were collected and extracted DNA for detection of Babesia sp., Erlichia sp. and Hepatozoon sp. using conventional polymerase chain reaction (PCR). The result found that 29 out of 43 were infected with tick borne pathogens. There were single infection with B.canis (10.35%), E.canis (13.80%) and H.canis (65.50%). Co-infection with B.canis, E.canis and H.canis was 3.45%, co-infection with E.canis and B.canis was 3.45% and co-infection with E.canis and H.canis was 3.45%. This study suggests that tick-borne pathogens remain the health problem in dog which may cause of sick and death at Nakhonpranom animal quarantine station, Thailand. Therefore, treatment and prevention of tick-borne disease are extremely needed.